2018
DOI: 10.1155/2018/2179021
|View full text |Cite
|
Sign up to set email alerts
|

Cabbage (Brassica oleracea var. capitata) Protects against H2O2‐Induced Oxidative Stress by Preventing Mitochondrial Dysfunction in H9c2 Cardiomyoblasts

Abstract: Oxidative stress plays an important role in the progression of cardiac diseases, including ischemia/reperfusion injury, myocardial infarction, and heart failure. Growing evidence indicates that cabbage has various pharmacological properties against a wide range of diseases, such as cardiovascular diseases, hepatic diseases, and cancer. However, little is known about its effects on oxidative stress in cardiomyocytes or the underlying mechanisms. Therefore, the present study examined the effects of cabbage extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
3
7
0
Order By: Relevance
“…Recent in vitro research has revealed that cabbage extract inhibits ROS production and increases SOD-1, catalase (CAT), and GPX activities. It inhibits the overactivation of MAPK proteins (ERK1/2, JNK, and P-38) and apoptosis of H9C2 cardiomyocytes without any cytotoxicity [ 53 ]. This suggests that cabbage extract can regulate MQC to reduce H 2 O 2 -induced oxidative stress injury in H9C2 cardiomyocytes and can be used in dietary replacement therapy to protect cardiomyocytes.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Recent in vitro research has revealed that cabbage extract inhibits ROS production and increases SOD-1, catalase (CAT), and GPX activities. It inhibits the overactivation of MAPK proteins (ERK1/2, JNK, and P-38) and apoptosis of H9C2 cardiomyocytes without any cytotoxicity [ 53 ]. This suggests that cabbage extract can regulate MQC to reduce H 2 O 2 -induced oxidative stress injury in H9C2 cardiomyocytes and can be used in dietary replacement therapy to protect cardiomyocytes.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Markers assessed after two weeks by real-time PCR analysis in ADSCs to confirm their capacity for chondrogenic, adipogenic, and osteogenic differentiation. Results of Yang et al study showed that different concentration of cabbage from 10 µg/mL to 500 µg/mL did not significantly different, but in 500 µg/mL to 2000 µg/ mL concentration, the cell viability reduced [33]. In our study, cell viability generally improved with increasing dose concentration.…”
Section: Discussionsupporting
confidence: 52%
“…Evaluation of the antiapoptotic effect of kohlrabi extract was comparable with Yang et al study. In this study, BCL2 expression was significantly increased in cells treated by cabbage extract [33].…”
Section: Discussionmentioning
confidence: 47%
“…1 g in 30 ml of methanol) were shown to inhibit nitric oxide in macrophage cell cultures after 24 h of exposure 14 and to protect a rat cardiomyoblast cell line from oxidative stress i.e. methanol (1:8) extract at least 2 h, treated with 100, 200, and 300 mg/ml cabbage extract for 24 h, 15 thus suggesting the importance of these two vegetables in complementary medicine. This is important since Brassica campestris spp (administered at 50 mg/kg orally in mice) effects on obesity were associated with increased expression of lipolysis genes (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…18 Heavy metal-induced stress has been associated with low growth rate, loss of chlorophyll, and plant death. 19,20 Compounding the problem of heavy metal contamination are (i) the absence of a robust food safety policy and technical knowledge in most developing countries to carry out routine monitoring of the environment, 1 (ii) the nature of pollution reporting in those countries, particularly in Africa, 15 and (iii) not providing consumers information on the sources and the distribution of contaminants in food products. There was, therefore, a need not only to determine the nature and extent of food contamination by heavy metals in this region but also to encourage the development of technical skills needed to conduct such studies.…”
Section: Introductionmentioning
confidence: 99%